An Ethnography Case Study on Reading Habit of One Selected EFL Learner - Arrasyid, Farouk Imam; Williyan, Aldha; Putri, Aprilia Riyana; Muzakki, Muhammad Alie (Journal of English Teaching and Learning Issues, 2023)
This ethnographic case study delves into the intricate reading habits of a fifth-semester EFL learner, exploring the multifaceted dynamics of her engagement with both fiction and non-fiction literature. The research unfolds the pivotal role of early exposure to reading, fostered by parental encouragement, in shaping a lifelong commitment to literary pursuits. The participant's diverse reading practices, encompassing print and e-books, reflect a nuanced approach to language acquisition and vocabulary enrichment. The study reveals a positive correlation between extensive reading habits and academic performance, particularly in TOEFL reading comprehension and overall language proficiency. The participant's transition from composing stories in Indonesian to writing in English, coupled with the abandonment of subtitles while engaging with English media, underscores the transformative impact of sustained reading habits on language skills. This research not only enhances the understanding of individual reading behaviors but also emphasizes broader implications for language development, academic success, and the cultivation of writing skills.  Further research should investigate the unique impacts of different genres on language acquisition, the influence of digital platforms on reading behaviors, and how reading intersects with socioeconomic and cultural factors. A longitudinal study tracking individuals from infancy to adulthood might uncover the long-term impacts of early literacy. Further investigation is required to explore the impact of personalized reading programs in EFL courses on language proficiency and academic performance. Further research in this field can potentially enhance EFL teaching and overall progress.